2014
DOI: 10.1111/anu.12131
|View full text |Cite
|
Sign up to set email alerts
|

Dietary methionine requirement of juvenile blunt snout bream (Megalobrama amblycephala) at a constant dietary cystine level

Abstract: A 9-week feeding trial was conducted to investigate the dietary methionine requirement of juvenile Megalobrama amblycephala at a constant dietary cystine level. Six semipurified diets were formulated to contain graded dietary methionine levels from 3.9 to 15.4 g kg À1 in about 2.5 g kg À1 increments in the presence of 2.2 g kg À1 cystine. Results showed that specific growth rate (SGR) and protein efficiency ratio (PER) significantly increased with increasing dietary methionine levels from 3.9 to 12.4 g kg À1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 52 publications
4
33
2
Order By: Relevance
“…() reported that excessive L‐methionine could be used efficiently by the fish body, but that the fish developed cataracts when methionine was in short supply. This symptom was not found in other studies of juvenile M. amblycephala (Liao et al., ). However, excessive supplementation of crystalline L‐methionine in feed had no significant influence on growth or feed utilization efficiency in barred soapfish ( Diploprion bifasciatum ) (Twibell et al., ), grouper ( Epinephelus coioids ) (Luo et al., ) or Japanese flounder (Alam et al., ).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…() reported that excessive L‐methionine could be used efficiently by the fish body, but that the fish developed cataracts when methionine was in short supply. This symptom was not found in other studies of juvenile M. amblycephala (Liao et al., ). However, excessive supplementation of crystalline L‐methionine in feed had no significant influence on growth or feed utilization efficiency in barred soapfish ( Diploprion bifasciatum ) (Twibell et al., ), grouper ( Epinephelus coioids ) (Luo et al., ) or Japanese flounder (Alam et al., ).…”
Section: Discussioncontrasting
confidence: 57%
“…Blunt snout bream, Megalobrama amblycephala , also known as Wuchang bream, is a major cultured freshwater fish species in China. However, knowledge of their methionine requirement is only known for juvenile fish (Liao et al., ), with the dietary methionine requirements estimated as 0.84–0.85% of the diet. No information is available on dietary methionine requirements for pre‐adult M. amblycephala .…”
Section: Introductionmentioning
confidence: 99%
“…Production in China was approximately 0.72 million tons in 2012 (Ministry of Agriculture of the People's Republic of China, 2013). Recently, several nutritional requirement studies have been published for M. amblycephala such as protein and lipid (Li et al, 2010(Li et al, , 2012a, carbohydrate/lipid ratios (Li et al, 2012b), carbohydrate (Zhou et al, 2013a), protein (Habte-Tsion et al, 2013, essential amino acids (Habte-Tsion et al, 2015;Liao et al, 2014;Ren et al, 2013), and vitamins and minerals (Jiang et al, 2013;Jiang et al, 2012;Miao et al, 2015;Wan et al, 2014;Zhou et al, 2013b;Shao et al, 2012). However, the growth and immune responses associated with VA in Wuchang bream have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing information on the basic nutrient requirements of this species have been reported in the last decade, and 31-34% dietary protein and 7-8% lipid were determined to be optimal for growth (Habte-Tsion et al, 2013;Li et al, 2010;Li et al, 2013;Ren et al, 2015a). The dietary EAA requirements of blunt snout bream including arginine , lysine , methionine (Liao et al, 2014), threonine and phenylalanine have been determined for this fish species. However, there is no available data on dietary leucine requirement of blunt snout bream.…”
Section: Introductionmentioning
confidence: 99%